Bringing Connections Onboard: The Value of Political Influence - Colin P. Green; Swarnodeep HomRoy (Institute of Labor Economics (IZA), 2020)
In 2002, an amendment to UK parliamentary regulations removed restrictions on the participation of members of parliament (MPs) in parliamentary proceedings related to their corporate interests. Using this amendment as a quasi-natural experiment, we demonstrate gains in firm value and profitability for firms with prior connections to MPs. These benefits are higher for firms with family ownership and lower accounting transparency. Both firms and politicians to change their behaviour. Post-amendment, firms are more likely to appoint MPs and also reduce political donations. Politicians with corporate connections were more likely to both become members of, and conditional on this, attend meetings of parliamentary select and joint committee. Our results highlight mechanisms of returns from political influence in well-developed institutional contexts.
Keywords: G14; D72; G18; G30; 330; political connections; board of directors; firm value